Evident lower blood levels of multiple nutritional compounds and highly prevalent malnutrition in sub-acute stroke patients with or without dysphagia - van Wijk, Nick; Studer, Bettina; van den Berg, Claudia A.; Ripken, Dina; Lansink, Mirian; Siebler, Mario; Schmidt-Wilcke, Tobias (Frontiers in Neurology, 2023)
Introduction Malnutrition is prevalent after stroke, particularly if post-stroke oropharyngeal dysphagia (OD) reduces nutritional intake. To further understand stroke-related malnutrition, a thorough nutritional assessment was performed in ischemic stroke patients with or without OD during sub-acute inpatient rehabilitation. Methods In this exploratory, observational, cross-sectional, multi-center study in Germany (NTR6802), ischemic stroke patients with (N = 36) or without (N = 49) OD were age- and sex-matched to healthy reference subjects. Presence of (risk of) malnutrition (MNA-SF), blood concentration of stroke-relevant nutritional compounds and metabolites, nutritional intake, quality of life (EQ-5D-5L), and activities of daily living (Barthel index) were assessed. Results More than half of the stroke patients displayed (risk of) malnutrition, with higher prevalence in patient with OD vs. without OD. Fasted blood concentrations of vitamins B1, B2, B6, A, D, and E, selenium, choline, coenzyme Q10, albumin, pre-albumin, transferrin, docosahexaenoic acid, and eicosapentaenoic acid were all lower in stroke patients compared to their matched healthy reference subjects, irrespective of OD status. Reported energy, macronutrient, and water intake were lower in stroke patients vs. healthy reference subjects. As expected, quality of life and activities of daily living scores were lower in stroke vs. healthy reference subjects, with OD scoring worse than non-OD patients. Discussion This study shows that malnutrition is highly prevalent in sub-acute stroke patients during rehabilitation. Even though patients with OD were more likely to be malnourished, blood levels of specific nutritional compounds were similarly lower in stroke patients with or without OD compared to healthy reference subjects. Furthermore, subgroup analysis showed similarly lower blood levels of specific nutritional compounds in patients that are normal nourished vs. patients with (risk of) malnutrition. This might imply disease-specific changes in blood levels on top of overall protein-energy malnutrition. The results of the current study underline that it is important to screen for nutritional impairments in every stroke patient, either with or without OD.